2014
DOI: 10.1097/wno.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Optic Nerve Head Drusen Using Enhanced Depth Imaging and Swept Source Optical Coherence Tomography

Abstract: Background Optic nerve head drusen (ONHD) are calcific deposits buried or at the surface of the optic disc. Although ONHD may be associated with progressive visual field defects, the mechanism of drusen-related field loss is poorly understood. Methods for detecting and imaging disc drusen include B-scan ultrasonography, fundus autofluorescence, and optical coherence tomography (OCT). These modalities are useful for drusen detection but are limited by low resolution or poor penetration of deep structures. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0
11

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(53 citation statements)
references
References 41 publications
0
42
0
11
Order By: Relevance
“…Furthermore, because the posterior margins of ODD can be better determined by EDI-OCT, their area and volume can also be calculated. 21 It has been reported that drusen have a central hyperreflective focus and an outer hyperreflective edge, with a hyporeflective area in between (Figure 8). A negative correlation between drusen diameter and RNFL thickness as well as greater RNFL loss in drusen located in the optic canal have been demonstrated.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, because the posterior margins of ODD can be better determined by EDI-OCT, their area and volume can also be calculated. 21 It has been reported that drusen have a central hyperreflective focus and an outer hyperreflective edge, with a hyporeflective area in between (Figure 8). A negative correlation between drusen diameter and RNFL thickness as well as greater RNFL loss in drusen located in the optic canal have been demonstrated.…”
Section: Introductionmentioning
confidence: 93%
“…The major advantage of USG is the ability to show even the posterior borders of buried drusen, but its drawbacks are low resolution and inability to provide data on the neural retina. 20,21 Although fundus autofluorescence (FAF) is a convenient method of visualizing more superficial drusen, it is insufficient for detecting buried drusen. Superficial drusen appear on FAF as round or oval hyperautofluorescent structures with irregular edges (Figure 4).…”
Section: Introductionmentioning
confidence: 99%
“…125; 183; 194 Merchant et al examined 32 eyes with clinically definite optic disc drusen and 25 eyes with suspected optic disc drusen in children and adults. 125 They found that B-scan ultrasonography, SD-OCT, and EDI-OCT all detected every case of clinically definite optic disc drusen; however, in 25 eyes with suspected buried optic disc drusen, EDI-OCT detected 17 cases, while SD-OCT and B-scan ultrasonography were positive in 14 and 7 eyes, respectively.…”
Section: Diagnostic Testingmentioning
confidence: 99%
“…16,17 Enhanced depth imaging (EDI) OCT and swept source (SS) OCT have also enabled qualitative descriptions of ONHD. 18-20 Although EDI-OCT, like SS-OCT, may allow for better visualization of deep ocular structures compared to SD-OCT, EDI-OCT, and SD-OCT in general, exhibits worse signal roll-off and reduced signal uniformity than SS-OCT. 21 SS-OCT provides both high penetration of tissue and high axial uniformity of images, at the expense of slightly reduced image contrast. To our knowledge, the only study which has attempted to quantify the size, shape, and location of ONHD used an experimental SD-OCT instrument.…”
Section: Introductionmentioning
confidence: 99%